2006
DOI: 10.3201/eid1208.060492
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza among Waterfowl Hunters and Wildlife Professionals

Abstract: We report serologic evidence of avian influenza infection in 1 duck hunter and 2 wildlife professionals with extensive histories of wild waterfowl and game bird exposure. Two laboratory methods showed evidence of past infection with influenza A/H11N9, a less common virus strain in wild ducks, in these 3 persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 14 publications
2
77
0
1
Order By: Relevance
“…A better measure of human risk would be to directly assess human exposure by testing for antibodies to all AIV subtypes that could occur in nature. Although it is not practical to simultaneously test for 144 virus subtypes, 2 serologic studies of persons exposed to wildlife showed antibodies to a limited number of AIVs (3,14). Since these exposures did not cause discernable illness, diagnosis based on clinical signs would likely underestimate infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better measure of human risk would be to directly assess human exposure by testing for antibodies to all AIV subtypes that could occur in nature. Although it is not practical to simultaneously test for 144 virus subtypes, 2 serologic studies of persons exposed to wildlife showed antibodies to a limited number of AIVs (3,14). Since these exposures did not cause discernable illness, diagnosis based on clinical signs would likely underestimate infection.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the types of exposure that result in human infections, especially with AIV being transmitted from wild birds and animals because only a few cases of transmission to humans have been documented (3)(4)(5). Overall, the types of exposures associated with the transmission of AIV to humans have been ingestion, inhalation of aerosolized virus, or direct contact through mucous membranes (2,4).…”
mentioning
confidence: 99%
“…In addition, 49% of 508 poultry cullers, as well as 64% of 63 persons exposed to H7N7 infected humans, had serological evidence of H7N7 infection following the 2003 Netherlands poultry outbreak [16]. A recent serological study of US duck hunters and wildlife biologists exposed to ducks and geese identified several subjects with elevated antibody titers against H11 viruses [19]. A controlled, 2002 cross-sectional study of US poultry-exposed veterinarians revealed serological evidence of previous infections with avian H5, H6, and H7 viruses [20].…”
Section: Challenges Posed By Influenza a Infections Among Swine And Pmentioning
confidence: 99%
“…Taken together, these data suggest that even wild waterfowl AIVs displaying poor replicative capacity in gallinaceous poultry may have the potential to directly switch hosts and infect mammals without prior adaptation. Although most reported human infections with AIVs occurred as a result of close contact with domestic poultry, serologic evidence of AIV infection (subtype H11N9) in three individuals with a history of substantial exposure to wild waterfowl and game birds does support the idea of direct transmission of AIVs from their natural reservoirs into humans [13].…”
Section: Discussionmentioning
confidence: 87%